An Experimental and Kinetic Study of the Sorption of Carbon Dioxide onto Amine-Treated Oil Fly Ash - Mohammed A. Saad; Mohammed J. Al-Marri; Ali L. Yaumi; Ibnelwaleed A. Hussein; Reyad Shawabkeh (Journal of Chemistry)
A new CO2 adsorbent is produced from waste oil fly ash (OFA). Ammonium hydroxide solution is used to convert OFA to activated carbon. Then, the product is used for the adsorption of CO2 from a nitrogen/carbon dioxide (N2/CO2) gas mixture. The OFA samples are characterized by several techniques. Chemical treatment of OFA considerably changed its surface morphology. In particular, its surface area, as determined by BET measurements, increased from 59 to 318 m2/g. The amine-functionalized ash had a monolayer adsorption capacity of 74.51 mg/g and was obtained at relative pressure, 0.05<p/ps<0.35. A kinetics study showed that the CO2 adsorption capacity of OFA increased with increasing CO2 flow rates and concentrations and decreasing the relative humidity. Unlike physical adsorption, the chemisorption process resulted in increased adsorption capacity with increasing temperatures over the range 0–40°C. We also found that the adsorption process was endothermic (80–173 kJ/mol). The isotherm data for the adsorption process were fitted using different models. The saturation capacity determined from the Sips model, which corresponds to the sum of the saturation capacities of all of the adsorbed layers, was 540.3 mg/g of ash.